Efektivitas Penerapan Sistem Artificial Intelligence Fuzzy Logic Terhadap Peningkatan Pendapatan Petani Biji Kakao - Cindy Puspitafuri; Kasmawati; Rusdin (Prosiding, 2025)
The distribution chain of plantation commodities continues to encounter persistent structural challenges, particularly effecting the bargaining position of farmers, who remain at a disadvantage when negotiating with intermediaries. This issue is notably experienced by cocoa bean farmers in Southeast Sulawesi. In response to this, the present study examines the development and implementation of an Artificial Intelligence (AI)-based information system utilizing fuzzy logic algorithms to predict and recommend cocoa bean selling prices in real time. The system also visualizes real time market price fluctuations through dynamic graphs. Designed not only to enhance farmers’ acces to timely and accurate market information, the system also aims to improve their bargaining power and contribute to more transaparent and equitable pricing practice. Furthermore, the system serves as decision support tool for local governments by providing reliable, data driven insights for policy formulation. Research used SWOT approach and was analyzed descriptively qualitatively. The prediction system achieved an accuracy rate of 92%, determined by comparing product price values calsulated using fuzzy logic algorithms with actual market prices. Price prediction information system is implemented as a mobile application, making it accesible to farmers, buyers and relevant government agencies. This innovation represents a strategic digital intervention to promote price transparency, enhance farmer welfare and support evidence based policymaking in the agricultural sector.